ANALISIS DAMPAK PENGGUNAAN TIKTOK TERHADAP PERILAKU BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Lidia Siti Riani; Asep Sahrul Gunawan (STKIP Subang, 2026)
The rapid development of information and communication technology in the era of globalization has significantly transformed how students access information and engage in learning activities. One of the most widely used social media platforms among elementary school students is TikTok, a short-video-based application that allows users to create, share, and explore creative content. This phenomenon raises concerns regarding its influence on students’ academic behavior, particularly in terms of learning discipline and motivation. This study aims to analyze the impact of TikTok usage on the learning behavior of elementary school students and to identify the relationship between the intensity of social media use and students’ learning motivation. This research employs a qualitative approach using the Systematic Literature Review (SLR) method. Data were collected through the identification, evaluation, and synthesis of relevant scientific literature obtained from Google Scholar and SINTA-indexed journals published between 2020–2025. A total of 14 selected articles were analyzed to provide a comprehensive understanding of the phenomenon. The results indicate that TikTok usage has a dual impact on students’ learning behavior. On the negative side, excessive use is associated with increased academic procrastination, decreased concentration, and reduced study time. On the positive side, TikTok can enhance creativity, self-expression, and serve as an innovative and engaging learning medium when used appropriately. In addition, the findings highlight that students’ ability to manage time and select appropriate content plays an important role in determining the impact of TikTok usage. In conclusion, TikTok significantly influences students’ learning behavior depending on the intensity and purpose of its use. Therefore, proper supervision and the integration of digital literacy in education are essential to maximize positive impacts and minimize negative effects.